Promoting Equity in Public Health: Adressing Healthcare Utilization Disparities in Indonesia - Nabila, Ichda Naila; Qomaruddin, Mochammad Bagus; Widati, Sri; Devy, Shrimarti Rukmini; Rachmadi, Eka Yanuar (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: The implementation of Indonesia’s National Health Insurance (JKN) has expanded healthcare access. As of December 31, 2024, JKN coverage had reached 98.45%, yet disparities persist across socioeconomic groups and geographic regions. These disparities contribute to unequal service quality, low utilization, and financial burdens among low-income households. Objective: This study identifies determinants of disparities in healthcare utilization in Indonesia using Andersen’s Behavioral Model and provides an evidence base for policymakers. Methods: A systematic review was conducted following PRISMA guidelines. Searches of CrossRef, Scopus, and PubMed (2015–2025) identified studies on healthcare utilization and disparities in Indonesia. Eligible articles were screened in Covidence and thematically synthesized using Andersen’s Behavioral Model to classify determinants into predisposing, enabling, and need factors. Results: Enabling factors, such as socioeconomic status, insurance ownership, and geographic access, were the strongest determinants, compared with predisposing factors (age, sex, marital status, and educational background) and need factors (self-rated health, chronic conditions, perceived healthcare needs). High health needs did not always lead to service use, particularly among low-income and remote populations. Financial protection alone is insufficient without improvements in health literacy, equitable workforce distribution, and stronger primary care. Conclusion: Although JKN has expanded access, disparities remain. An integrated approach is needed to strengthen primary care, ensure equitable health worker distribution, improve health literacy, and enhance geographic access. These actions can shift JKN’s focus from coverage expansion to equitable service access, supporting Indonesia’s progress toward Universal Health Coverage (UHC) and the Sustainable Development Goals (SDGs).